Loss of POLR1D results in embryonic lethality prior to blastocyst formation in mice. Issue 11 (6th October 2020) - Miao, Xiaosu; Sun, Tieqi; Golan, Morgane; Mager, Jesse; Cui, Wei
Abstract: In eukaryotic cells, RNA polymerase (Pol) I and Pol III are dedicated to the synthesis of ribosomal RNA precursors and a variety of small RNAs, respectively. Although RNA Pol I and Pol III complexes are crucial for the regulation of cell growth and cell cycle in all cell types, many of the components of the Pol I and Pol III complexes have not been functionally characterized in mammals. Here, we provide the first in vivo functional characterization of POLR1D, a subunit shared by RNA Pol I and Pol III, during early mammalian embryo development. Our results show that Polr1d mutant embryos cannot be recovered at E7.5 early post‐gastrulation stage, suggesting failed implantation. Although Polr1d mutants can be recovered at E3.5, they exhibit delayed/stalled development with morula morphology rather than differentiation into blastocysts. Even with extended time in culture, mutant embryos fail to form blastocysts and eventually die. Analysis of E3.0 embryos revealed severe DNA damage in Polr1d mutants. Additionally, lineage assessment reveals that trophectoderm specification is compromised in the absence of Polr1d . In summary, these findings demonstrate the essential role of POLR1D during early mammalian embryogenesis and highlight cell‐lethal phenotype without Polr1d function. Abstract : In the present study, we use a novel knockout (KO) allele to explore the role of POLR1D during murine embryogenesis in vivo. Our data show that POLR1D is essential during early preimplantation development, where the loss of POLR1D results in DNA damage, impaired trophectoderm specification, and failure to form a blastocyst.